White Spot Lesions during Orthodontic Treatment - Emrah Emral; Okan Akçam (Galenos Yayinevi, 2008)
White spot lesions are non-esthetic demineralized regions that may develop during the orthodontic treatment. 2-96% of the patients were found to be effected after orthodontic treatment. The incidence and severity of the white spot lesions are related to the duration of the teeth that had braces and preventive measures are important during the treatment period. The purpose of this review is to present information about the formation, diagnosis, incidence and treatment of white spot lesions and to reveal its role and importance in orthodontics.